EARLY PPARα ACTIVATION PROTECT AGAINST HEPATIC MICROSTEATOSIS INDUCED BY POST-NATAL OVERFEEDING - Ana L. M. Assakawa; Lucas P. J. Saavedra; Scarlett Raposo; Naiara Lucredi; Maria N. C. Peres; Silvano Piovan; Gessica Gonçalves; Letícia Barbosa; Jurandir Comar; Douglas L. Almeida; Paulo C. F. Mathias (Arquivos do Mudi, 2023)
Post-natal overfeeding leads to development of obesity and metabolic dysfunction. PPARαactivation improves steatosis and metabolic dysfunction associated with obesity. Thus, wehave hypothesized that PPARα would prevent the metabolic disorders and obesity caused bylitter reduction. Wistar male offspring rats were divided into normal litter (NL - 9 pups) andsmall litter (SL - 3 pups) and were daily treated with an PPARα agonist, fenofibrate, frompost-natal day (PN) 1 until weaning (PN21), with either, fenofibrate (F - 12.5mg/kg) orvehicle (V). Forming the following groups: NL-V, NL-F, SL-V, SL-F. At PN120 animalswere euthanized and histological evaluation of samples from liver, visceral (VAT),subcutaneous (SAT) and brown (BAT) adipose tissue were performed. Fenofibrate was ableto prevent the development of microsteatosis in the liver caused by postnatal overfeeding. Inregard to VAT, there was no difference in the mean adipocyte area, however in distributionanalyzes it was observed higher frequency of larger adipocytes in SL groups, and nodifference was observed in SAT. SL-V animals had increased lipid area in BAT, which wasreduced in SL-F. Increased PPARα activation induced by an agonist during lactationimproved some histopathological abnormalities induced by postnatal overfeeding. This wasproven by the decrease in microsteatosis in the liver and improvement in VAT and BATmorphology, thus implying a better metabolic health.